The Artistic Groups from the School of Culture and Sports from the Technological Institute of Costa Rica. - Sancho Martínez, Laura (2021)
In the present article we develop a description of the commitment of The School of Culture and Sports of the Technological Institute of Costa Rica, with respect to its groups of art; this, from the perspective of the importance of the latter in the student’s life and their integral education. Therefore, the main purpose of this document it’s to visualize the integral development of the students through the courses that are offered in the sphere of art, mainly in the dance area, besides the benefits and opportunities that such courses can provide to the student body. The discussion is centered upon what we previously mentioned: Dance groups. These groups have been gradually created, since the founding of the School and presently they are 11, which according to their members, are a window towards a more humane and emotional aspect of life; in addition to how these groups help professionals to be more creative, realist and sensitive. Therefore, it is possible to conclude without doubt that these projects offered by the School of Culture and Sports, are paths towards the preparation of students that are more integral in their formation, with special skills in diverse areas which promote healthy lifestyles, positive values and a great sense of creativity.